Twin‐to‐twin transfusion syndrome: Perinatal outcome and recipient heart disease according to treatment strategy. Issue 1 (21st December 2012) - Barrea, Catherine; Debauche, Christian; Williams, Olivia; Jasienski, Stéphanie; Steenhaut, Patricia; Sluysmans, Thierry; Bernard, Pierre; Hubinont, Corinne
<x xml:space="preserve">Abstract</x> Aim The aims of the study were to compare perinatal outcome and assess recipient cardiac disease according to treatment strategy (amnioreduction (AR), laser or selective feticide). Methods We retrospectively reviewed 81 consecutive cases of twin‐to‐twin transfusion syndrome diagnosed before 28 weeks between 1993 and 2007. Results Although fetuses treated by laser were younger at diagnosis (median 20.4 vs. 22.4 weeks, P = 0.01), they were significantly older at birth (median 33.6 vs. 28.5 weeks, P = 0.004) than those treated by AR. Neonatal morbidity was globally lower after laser than AR, and cardiac insufficiency tended to be less frequent (31% vs. 57%, P = 0.09). There was a trend towards increased perinatal survival after laser treatment (68% vs. 49%, P = 0.1). Heart failure was the cause of death in half (23/46) of the recipients. Fetal heart failure leading to death was 2.7 times more frequent after AR than after laser (n = 11 vs. n = 4), and all four neonatal cardiac deaths occurred after AR. Compared with laser, selective feticide did not further improve the outcome. Conclusions Heart failure was an important cause of perinatal morbidity and death. However, laser therapy resulted in a longer diagnosis–delivery interval and lower global neonatal morbidity than AR, with a trend towards increased perinatal survival. Improved outcome after laser treatment compared with AR might be related to its impact on recipient heart disease.